Contrasts in China and Soviet reform: sub-national and national causes - Lai, Hongyi (Taylor & Francis, 2005)
Why did reform in China and the former Soviet Union produce drastically different outcomes? Why did some provinces in China embrace faster economic reform than others? This article argues that the state sector and reform initiatives in the sub-national units, reform strategies, entrenchment and maturation of central planning, the size of the defence industry, policy choice and the historical context help explain the differences in Soviet and Chinese reform courses and outcomes. A predominant state sector in the former Soviet republics had stifled local reform initiatives. Gorbachev resorted to democratisation in order to unbolt the gate for popular support for marketisation, yet resulting in the breakup of the Soviet Union and destabilising the economy. In China, some provinces had sizable non-state sectors and were inclined to push forth marketization. Reform resulted in expanding non-state sectors, generating high growth and encouraging the regime to maintain its monopoly of power. China’s reform also benefited from a yet-to-be-entrenched and rudimentary central planning, a small defence sector, popular backlash against past policies, and reformist pragmatic strategy.